Celsius Network - Celsius Imago - Celsius Bloodhound - De Giusti, Marisa Raquel (2007)
The Library Linkage Project (Proyecto de Enlace de Bibliotecas-PrEBi) of La Plata National University (UNLP) if part of Library Linkage initiative (LL) of Ibero American Science and Technology Education Consortium (ISTEC) which the UNLP belongs to. The main objective of PrEBi is to provide technical and scientific information required for Researchers, Teachers and Students from UNLP, as well as to provide to member institutions that are part of the project of documentations available in libraries in the dependencies of each University.